Field Guide to the Lichens of White Rocks : (Boulder, Colorado) - Tripp, Erin Anne, 1979- (Book collections on Project MUSE., 2016)
"Extensively illustrated field guide presents detailed information and a careful examination of the lichens that occur at the ecologically important and lichenologically rich urban outcropping of sandstone known as White Rocks Nature Preserve in Boulder County, Colorado. Includes both macroscopic and microscopic features needed to identify species"--Provided by publisher.